High contrast imaging of dental fluorosis in the short wavelength infrared. Issue 10 (29th July 2021) - Kashirtsev, Filipp; Tressel, John; Simon, Jacob C.; Fried, Daniel
Abstract: Dental fluorosis is an increasing problem due to over exposure to fluoride from the environment. Fluorosis causes hypomineralization of the enamel during tooth development and mild fluorosis is visible as faint white lines on the tooth surface while the most severe fluorosis can result in pitted surfaces. It is difficult to quantify the severity of mild to moderate fluorosis and assessments are limited to subjective visual examinations. Dental fluorosis appears with very high contrast at short wavelength infrared (SWIR) wavelengths beyond 1400 nm and we hypothesize that these wavelengths may be better suited for detecting mild fluorosis and for estimating the severity on tooth surfaces. In this study, the contrast of fluorosis of varying severity on extracted human permanent teeth was measured at SWIR wavelengths ranging from 1300 to 2150 nm using an extended range of InGaAs camera and broadband light sources. The contrast was also measured in the visible range and with quantitative light‐induced fluorescence (QLF) for comparison. The depth of hypomineralization and the integrated reflectivity were also measured with cross‐polarization optical coherence tomography. The contrast of hypomineralization is significantly higher ( P  < 0.05) at 1460 and 1950 nm wavelengths than for the visible, fluorescence or other SWIR wavelengths from 1300 to 2150 nm. The highest correlation of the contrast with the depth of hypomineralization measured with cross‐polarization‐optical coherence tomography (CP‐OCT) was at 1950 nm. This SWIR in vitro imaging study exploring wavelengths beyond 1400 nm has shown that hypomineralization on tooth surfaces can be viewed with extremely high contrast at SWIR wavelengths from 1460 to 2000 nm and that SWIR imaging has great potential for monitoring hypomineralization on tooth surfaces. New clinical methods are needed for the measurement of fluorosis that are valid, reliable, and feasible for surveillance at the community level. In addition, methods are needed for the quantitative assessment of fluorosis in vivo. Abstract : Dental fluorosis is an increasing problem due to over exposure to fluoride. The contrast of fluorosis of varying severity on extracted teeth was measured at SWIR wavelengths ranging from 400 to 2150‐nm using an extended range of InGaAs camera and broadband light sources. The contrast of hypomineralization is significantly higher ( P  < 0.05) at 1460 and 1950 nm wavelengths than for the visible, fluorescence or other SWIR wavelengths. New clinical methods are needed for the measurement of fluorosis for surveillance at the community level.